Newly recorded genera in the planthopper family Tropiduchidae (Hemiptera: Fulgoroidea) from Pakistan with redescription of Epora montana Distant - Sohail, Kamran; Webb, Mick; Zhang, Yalin (Zootaxa, 2020)
The tropiduchid genera Epora Walker and Zema Fennah are recorded from Pakistan for the first time and Epora montana Distant is redescribed and illustrated.